TIPOLOGI DAN POSISI KERUANGAN ORNAMEN KACA DI RUMAH KALANG DI KAMPUNG KOTAGEDE YOGYAKARTA (Jurnal Arsitektur ARCADE, 2026)
Rumah Kalang in Kotagede, Yogyakarta, is a historic residential architecture characterized by the integration of Javanese spatial traditions and European decorative influences, including stained glass ornaments. However, studies on the typology and spatial placement of stained glass in Rumah Kalang remain limited. This study aims to identify the typology of stained glass ornaments, analyze their spatial positions, and explain the rationale underlying their placement. A qualitative descriptive approach was employed through field observations, visual documentation, interviews, literature review, and access graph analysis. Five Rumah Kalang buildings were selected as research objects. The findings reveal five ornament typologies, namely floral, faunal, geometric, emblematic, and identity. Floral and geometric motifs are the most dominant, reflecting the influence of Art Nouveau and Art Deco styles. Spatial analysis indicates that stained glass ornaments are primarily located in spaces with low depth levels and high visibility, such as façades, pendhapa, pringgitan, and guest rooms. These findings suggest that stained glass functions not only as a decorative element but also as a medium that reinforces visual identity, social representation, and spatial hierarchy within Rumah Kalang.